Vállalkozói képzés a 21. században a felsőoktatásban – lehetőségek, módszerek, jó gyakorlatok - Árváné Ványi, Georgina; Katonáné Kovács, Judit; Gál, Tímea; Popovics, Péter (International Journal of Engineering and Management Sciences, 2016)
Challenges of the 21st century require answers from higher education as well. In Europe, most of the entrepreneurship programmes on the higher education institutions are less than ten years old. Whilst business studies may battle for academic legitimacy, it has a clear advantage when it comes to graduate employability. The aim of this paper is to give answer to the following questions: why entrepreneurship education is important, what are the methods which are already used and what are the results of them. The answers to the questions are based on literature reviews, a case study and in-depth interviews with alumni carried out at the University of Debrecen, where since 2010 Team Academy Debrecen, a new education model from Finland is implemented. Tiimiakatemia education is an innovative Finnish model founded in 1993 by Johannes Partanen that develops team entrepreneurs. Based on the results some of the important elements of entrepreneurship teachability are: learning by doing, passion, learning in teams, coaching and mentoring.